2017
DOI: 10.1002/jor.23795
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity vibration increases cartilage thickness in obese mice

Abstract: Obesity is associated with an elevated risk of osteoarthritis (OA). We examined here whether high fat diet administered in young mice, compromised the attainment of articular cartilage thickness. Further, we sought to determine if low-intensity vibration (LIV) could protect the retention of articular cartilage in a mouse model of diet-induced obesity. Five-week-old, male, C57BL/6 mice were separated into three groups (n = 10): Regular diet (RD), High fat diet (HF), and HF + LIV (HFv; 90 Hz, 0.2g, 30 min/d, 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Some studies showed that PEMF stimulation inhibited cartilage destruction and preserved cartilage and subchondral trabecular bone by regulating the catabolic factor, MMP13 [Ciombor et al, 2003; Fini et al, 2005; Fini et al, 2008; Zhou et al, 2017]. Due to the fact that musculoskeletal tissues are highly sensitive to mechanical stimulation, previous studies suggested that WBV delayed cartilage degeneration, stimulated the proliferation of chondrocytes, increased bone turnover, regulated the expression of inflammatory factors, reduced the expression of MMPs, and promoted tissue repair [Yamazaki et al, 2002; Junbo et al, 2017; Pamon et al, 2018]. We also found similar results, that PEMF and WBV treatments attenuated the expression of IL‐1β, ADAMTS4, and MMP13 and increased the expression of Aggrecan, and prevented articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed that PEMF stimulation inhibited cartilage destruction and preserved cartilage and subchondral trabecular bone by regulating the catabolic factor, MMP13 [Ciombor et al, 2003; Fini et al, 2005; Fini et al, 2008; Zhou et al, 2017]. Due to the fact that musculoskeletal tissues are highly sensitive to mechanical stimulation, previous studies suggested that WBV delayed cartilage degeneration, stimulated the proliferation of chondrocytes, increased bone turnover, regulated the expression of inflammatory factors, reduced the expression of MMPs, and promoted tissue repair [Yamazaki et al, 2002; Junbo et al, 2017; Pamon et al, 2018]. We also found similar results, that PEMF and WBV treatments attenuated the expression of IL‐1β, ADAMTS4, and MMP13 and increased the expression of Aggrecan, and prevented articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies demonstrated that mechanical stimulation not only increased matrix synthesis and expression of collagen and chondrogenic marker, but also decreased the production of MMPs group in osteoarthritic chondrocytes for normal cartilage [Liphardt et al, 2009; Burr and Gallant, 2012]. Additionally, WBV modulated the expression of inflammatory cytokines, promoted tissue repair, accelerated cartilage formation, and decreased cartilage resorption [Junbo et al, 2017; Pamon et al, 2018]. It has been widely accepted that WBV has been recommended as a safe and efficient tool for increasing muscle strength in KOA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chondrocytes embedded in the ECM of the cartilage are known to be responsive to mechanical forces such as pressure, shear stress or vibrations [29][30][31][32][33][34]. During OA progression, the ECM is actively remodeled by chondrocytes under inflammatory conditions [35].…”
Section: Discussionmentioning
confidence: 99%
“…This special issue begins with several outstanding reviews that provide updates on the significance of mechanobiology in musculoskeletal research involving cartilage, tendon, muscle and bone, [1][2][3][4][5][6][7][8][9][10] and that span topics from the role of candidate mechanosensors and chemical mediators, 1,5,9,10 in vitro and in vivo models of tissue injury and repair, 3,4 and supporting technologies. 6,7 The majority of original articles following the review papers are related to the mechanobiology of bone and cartilage, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] tissues whose physical regulation have traditionally garnered intensive research focus, followed by complementary research papers in areas of growing prominence: Ligaments, intervertebral discs, and stem cells. [24][25][26][27][28] From this Special Issue in Musculoskeletal Mechanobiology, it is clear that it has become technically possible to trace the impact of mechanics from individual molecules to an entire organism.…”
mentioning
confidence: 99%